Implications of Tokenizers in BERT Model for Low-Resource Indian Language - Venkatesan, N.; Arulanand, N. (Journal of Soft Computing Paradigm, 2023)
For any deep learning language model, the initial tokens are prepared as a part of the text preparation process, Tokenization. Important de facto models like BERT and GPT de facto utilize WordPiece and Byte Pair Encoding (BPE) as approaches. Tokenization may have a distinct impact on models for low-resource languages, such as the south Indian Dravidian languages, where many words may be produced by adding prefixes and suffixes. In this paper, four tokenizers are compared at various granularity levels, i.e., their outputs range from the tiniest individual letters to words in their most basic form. Using the BERT pretraining process on the Tamil text, these tokenizers as well as the language models are trained. The model is then fine-tuned with numerous parameters adjusted for the improved performance for a subsequent job in Tamil text categorization. The custom-built tokenizer for Tamil text is created and trained with BPE, WordPiece Vocabulary, Unigram, and WordLevel mechanisms and the compared results are presented after the downstream task of Tamil text categorization is performed using the BERT algorithm.